A entoação modal em cinco falares do Nordeste brasileiro - Lira, Zulina Souza de (2009)
It is well known that there is no linguistic uniformity in the Portuguese spoken in Brazil. The Northeastern region of the country, for instance, is large and there is still lack of knowledge about its dialectal aspects, especially those related to intonation. In fact, there are still few research studies on dialectal prosody in our country. The aim was to describe the behavior of the fundamental frequency (F0), acoustic parameter responsible for the perception of the pitch, in declarative and interrogative sentences in the dialects of Salvador, Recife, João Pessoa, Fortaleza and São Luís. It is a descriptive and comparative research study based on the methodological procedures of Project AMPER. Disjunctive and Wh-questions, as well as its correspondent declaratives, were added to the original AMPER Corpus, which is made of declarative sentences and yes-no questions. The elicitation of sentences was achieved through visual stimuli which conducted the informant to produce the utterance as naturally as possible, avoiding the prosodic marks present when the speaker is reading. Four informants were contacted, in each city, with the following features: male-female (homogeneous distribution), over 30 years old, basic and superior education. The recording was made by a digital recorder Microtack II plugged into a directional microphone Samson C02. For the melodic contours (F0) analysis the software Praat was used. The results show that the declarative intonation does not offer a substantial difference among the cities; the yes-no questions, on the other hand, basically have two patterns, depending on the pause of the utterance: the stressed syllable and the post-stressed syllable. Three different patterns were observed as for the intonation of disjunctive questions, with relevant differences between those in São Luis-Fortaleza from those in Recife-João Pessoa and Salvador. Finally, as for Wh-questions, a more relevant variation was observed: four different patterns, one to each city, except for Recife and João Pessoa, which share the same pattern.